Elizabeth Peyton : 16 Artists. - Amanshauser, Hildegund; Bell, Kirsty; Peyton, Elizabeth; Salzburger Kunstverein, Salzburg (Salzburg : Salzburger Kunstverein, 2002)
The exhibition and catalogue for the Salzburg Kunstverein devised by Elizabeth Peyton present exclusively portraits of artists, friends as well as her role models David Hockney and Andy Warhol. The selection comprises a variety of media - oil on board or canvas, pencil and crayon drawings, watercolours and prints - and they provide an insight into the intimacy and intensity of Elizabeth Peyton's world of picture.
biog., ind. tent. p. 37
Duits
Engels
Elizabeth Peyton : 16 Artists, Salzburger Kunstverein Salzburg, 15. August bis 6. Oktober 2002
boek
Keywords: Peyton, Elizabeth